Penalty kick analysis in the FIFA Men`s World Cup: The rise of keeper-dependent strategy - Han, Z.; Li, G.; Zhang, Y.; Memmert, D.; Han, B. (International Journal of Sports Science & Coaching, 2025)
Penalty kicks in FIFA World Cups often play a decisive role in determining match outcomes. Our study analysed 64 in-match penalties from the 2014, 2018, and 2022 FIFA Men's World Cups, focusing on player running behaviours (fluent vs. non-fluent) to investigate the prevalence of specific penalty strategies during these tournaments. Penalty strategy (keeper-independent and keeper-dependent), situational (tournament year, tournament stage, match period, match status), individual (footedness), and performance indicators (shoot direction, goalkeeper's action, outcome) were collected from the three successive World Cups. Chi-square tests were conducted to evaluate the relationships between indicators and strategies. Adjusted standardised residuals were calculated to identify significant cell contributions and support further analysis.